2022
DOI: 10.1080/21655979.2021.2020390
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Circ_0017639 facilitates proliferative, migratory, and invasive potential of non-small cell lung cancer (NSCLC) cells via PI3K/AKT signaling pathway

Abstract: Non-small cell lung cancer (NSCLC) has increased morbidity and mortality rate worldwide. The current NSCLS therapies are associated with poor outcomes and need further improvement. CircRNAs were shown to regulate NSCLC progression. However, little is known re garding the functions and mechanisms of circ_0017639 in NSCLC, which requires further extensive studies. The circ_0017639 expression in NSCLC tissues and cell lines was evaluated via qRT-RCR. Moreover, using ectopic plasmid incorporation and shRNA assays,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…[43] Kaempferol, a flavonoid from natural plant sources, has proved to be effective in anti-NSCLC, specifically in inducing apoptosis in NSCLC cells, [44] promoting autophagy in NSCLC cells, [45] increasing the sensitivity to radiotherapy, [46] and inhibiting migration of A549 cells. [47] The PI3K-AKT signaling pathway is a key signaling pathway that regulates the progression of metastasis, [48] cell proliferation, differentiation, and metabolism. [49] It has been shown that some natural substances like Fucoxanthin could inhibit proliferation, and arrest cell cycle at the G0/G1 phase in NSCLC cells through the PI3K-AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[43] Kaempferol, a flavonoid from natural plant sources, has proved to be effective in anti-NSCLC, specifically in inducing apoptosis in NSCLC cells, [44] promoting autophagy in NSCLC cells, [45] increasing the sensitivity to radiotherapy, [46] and inhibiting migration of A549 cells. [47] The PI3K-AKT signaling pathway is a key signaling pathway that regulates the progression of metastasis, [48] cell proliferation, differentiation, and metabolism. [49] It has been shown that some natural substances like Fucoxanthin could inhibit proliferation, and arrest cell cycle at the G0/G1 phase in NSCLC cells through the PI3K-AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K-AKT signaling pathway is a key signaling pathway that regulates the progression of metastasis, [48] cell proliferation, differentiation, and metabolism. [49] It has been shown that some natural substances like Fucoxanthin could inhibit proliferation, and arrest cell cycle at the G0/G1 phase in NSCLC cells through the PI3K-AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, circ_0017639 exerted an inhibiting impact on glioma cell metastasis and proliferation, which might be related to the tissue-specific expression [ 51 ]. A recent report showed that circ_0017639 was highly expressed in NSCLC samples and cell lines, and circ_0017639 overexpression promoted NSCLC cell proliferation, invasion, and migration via the PI3K/AKT signaling [ 52 ]. The difference between our study and the previous report [ 52 ] was to explore the function of circ_0017639 in DDP resistance in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that circ_0017639 was highly expressed in NSCLC samples and cell lines, and circ_0017639 overexpression promoted NSCLC cell proliferation, invasion, and migration via the PI3K/AKT signaling [ 52 ]. The difference between our study and the previous report [ 52 ] was to explore the function of circ_0017639 in DDP resistance in NSCLC. Our data showed higher levels of circ_0017639 in DDP-resistant samples and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…For example, circ_CDR1-AS contributes to resistance to pemetrexed and CDDP through activating the EGFR/PI3K pathway in LUAD ( 88 ). Additionally, circ_0017639 ( 89 ) and circ_0008594 ( 90 ) both can facilitate the progression of NSCLC by PI3K signaling pathway. Therefore, circRNAs are potential targets for intervening in drug resistance problems, with circRNAs playing a significant role in the modulation of the PI3K/AKT pathway.…”
Section: Signaling Pathways Associated With Circrnas In Nsclcmentioning
confidence: 99%